Psychometric validation of the Turkish expanded mindful eating scale - Gökcen Doğan; Eda Çakmak; Ceren Şarahman Kahraman; Nurcan Yabanci Ayhan (PLoS ONE, 2025)
Background/Objectives The Expanded Mindful Eating Scale (EMES) assesses mindfulness by considering both individual health and environmental sustainability. A distinguishing feature of the EMES is its inclusion of sustainability, setting it apart from other eating awareness scales. This study was carried out to determine the validity and reliability of the Turkish culture-adapted version of the EMES in adults. Materials/Methods In this cross-sectional study, 662 Turkish adults (mean age=29.8, SD=12.18; 18.4% male) were recruited via an online questionnaire. In this study, participants were recruited via an online survey that included their sociodemographic characteristics, the EMES, Mindful Eating Questionnaire (MEQ), and sick, control, one, fat, food (SCOFF) Eating Disorders Scale. Confirmatory factor analysis (CFA) was used to test the validity of the EMES. Analyses were conducted using SPSS version 25.0 and SPSS AMOS version 25.0. The 5-factor structure identified by Explanatory Factor Analysis (EFA) was validated using CFA. Results As a result of confirmatory factor analysis (RMSEA: 0.053, CFI: 0.89, GFI: 0.94, and AGFI: 0.92), model fit indices were obtained within acceptable limits. In the reliability analysis, it was observed that the EMES scale had a good level of reliability with the Spearman-Brown coefficient. A significant correlation was observed between the EMES and MEQ. Conclusion The results showed that the use of the Turkish version of the EMES is valid and reliable. It is thought that the validation of the Expanded Mindful Eating Scale reflects a comprehensive approach that recognizes the interconnectedness of individual health and environmental well-being.